Pengembangan Kurikulum Bahasa Arab Model The Grass Roots (Studi Kasus Di Lembaga Kursus Bahasa Arab Al-Azhar Pare-Kediri) - Muzdalifah; Nuriya Maslahah; pengelola, pengelola (STAI Ihyaul Ulum Gresik, 2023)
The development of national curriculum from time to time has been changed, modified, and adjusted with the revolution era and learning development in the formal education such as school or non-formal education organization such as courses. Formal education has kurikulum which is implemented based on national curriculum, formed by the government with less modification at school and teachers execute the curriculum as it is. It is different with non-formal education, curriculum is being handed to each course. Al-Azhar is Arabic course which has many clients from locals or foreigners. Because of those reasons, this research is aimed at knowing the development Arabic curriculum with the Grass Roots model at Al-Azhar Arabic course at Pare. The method used in this research is descriptive qualitative with type of research Miles and Huberman case study model. The result of this research hoped can be the inspiration or role model for other Arabic courses in Indonesia, in hoped that Arabic can be developed and spread